La implementación de políticas públicas (2007)
This article offers a tour around the major ideas and theoretical frameworks regarding public policy implementation. In an introductory and ingenious way, the currently poor study level about the nature of the kind of decision that should be implemented is analyzed. Within this framework, the law is identified as the most formal existing mechanisms in the implementation of policies of which, subsequently, the most relevant visions and positions are identified, among them the topdown and bottomup approaches, as well as the most recent policy network and policy outcome ideas. Later on, reference is made to some theoretical frameworks envisaging bureaucratic factors as the central implementation axis, by observing their limitations; and by pointing out that, actually, a multiplicity of factors and actors take part in the process. Finally, a discussion is opened about the convenience of using either of the theoretical frameworks in the analysis of public policy implementation.